Hiv/Aids Knowledge And Sex Behavior Among Junior High School Students - Maria Mencyana Pati Saghu; Verayanti Albertina Bata; Grasiana Florida Boa; B. Dian Novita; Maria Manungkalit (Institute of Computer Science (IOCS), 2022)
Problems that stand out among teenagers are sexuality, HIV/AIDS, and drugs. The level of knowledge about HIV/AIDS in adolescents is high, but adolescents continue to engage in unsafe sexual activities and are at risk of contracting HIV/AIDS in dating. This will increase the incidence of contracting HIV / AIDS in adolescents. This study aims to determine whether there is a relationship between knowledge about HIV/AIDS and free sex behavior in adolescents. This type of research is a correlational study with a cross-sectional approach. The samples used were students of classes VIII and IX at SMP Tri Guna Bhakti Surabaya; as many as 151 people were selected using a total sampling technique. The measuring instrument used is a questionnaire containing 15 questions about knowledge about HIV/AIDS and ten questions about free sex behavior in adolescents. Analysis of the data used is chi-square. respondents who have risky behavior are respondents with less knowledge, where the most number is 59%. At the same time, respondents who behave not at risk are respondents with sufficient knowledge, as much as 49%. The Chi-Square test produces a significant correlation with p = 0.000. This study's results found a relationship between knowledge about HIV/AIDS and free sex behavior in adolescents at Tri Guna Bhakti Junior High School Surabaya.